Covalency and magnetic anisotropy in lanthanide single molecule magnets: the DyDOTA archetype. Issue 30 (20th June 2019) - Briganti, Matteo; Garcia, Guglielmo Fernandez; Jung, Julie; Sessoli, Roberta; Le Guennic, Boris; Totti, Federico
Abstract : The unexpected covalent contribution in the DOTADy-OH2 bond revealed by ab initio calculations of the easy axis of magnetization through simple H2 O rotations. Abstract : Lanthanide ions when complexed by polyamino-polycarboxylate chelators form a class of compounds of paramount importance in several research and technological areas, particularly in the fields of magnetic resonance and molecular magnetism. Indeed, the gadolinium derivative is one of the most employed contrast agents for magnetic resonance imaging while the dysprosium one belongs to a new generation of contrast agents for T2 -weighted MRI. In molecular magnetism, Single Molecule Magnets (SMMs) containing lanthanide ions have become readily popular in the chemistry and physics communities since record energy barriers to the reversal of magnetization were reported. The success of lanthanide complexes lies in their large anisotropy due to the contribution of the unquenched orbital angular momentum. However, only a few efforts have been made so far to understand how the f-orbitals can be influenced by the surrounding ligands. The outcomes have been rationalized using mere electrostatic perturbation models. In the archetype compound [Na{Dy(DOTA) (H2 O)}]·4H2 O (NaDyDOTA·4H2 O) an unexpected easy axis of magnetization perpendicular to the pseudo-tetragonal axis of the molecule was found. Interestingly, a dependency of the orientation of the principal magnetization axis on the simple rotation of the coordinating apical water molecule (AWM) – highly relevant for MRI contrast – around the Dy-OAWM bond was predicted by ab initio calculations, too. However, such a behaviour has been contested in a subsequent paper justifying their conclusions on pure electrostatic assumptions. In this paper, we want to shed some light on the nature of the subtle effects induced by the water molecule on the magnetic properties of the DyDOTA archetype complex. Therefore, we have critically reviewed the structural models already published in the literature along with new ones, showing how the easy axis orientation can dangerously depend on the chosen model. The different computed behaviors of the orientation of the easy axis of magnetization have been rationalized as a function of the energy gap between the ground and the first excited doublet. Magneto-structural correlations together with a mapping of the electrostatic potential generated by the ligands around the Dy(iii ) ion through a multipolar expansion have also been used to evidence and quantify the covalent contribution of the AWM orbitals.